64Cu-ATSM therapy targets regions with activated DNA repair and enrichment of CD133+ cells in an HT-29 tumor model: Sensitization with a nucleic acid antimetabolite. Issue 1 (28th June 2016) - Yoshii, Yukie; Furukawa, Takako; Matsumoto, Hiroki; Yoshimoto, Mitsuyoshi; Kiyono, Yasushi; Zhang, Ming-Rong; Fujibayashi, Yasuhisa; Saga, Tsuneo
Highlights: 64 Cu-ATSM accumulates in tumor regions with upregulation of DNA repair. 64 Cu-ATSM high-uptake regions show enrichment of CD133 + cancer stem-like cells. Nucleic acid (NA) incorporation is facilitated in 64 Cu-ATSM high-uptake regions. 64 Cu-ATSM therapy with an NA antimetabolite synergistically inhibited tumor growth. The sensitized 64 Cu-ATSM therapy effectively reduced %CD133 + cells. Abstract: 64 Cu-diacetyl-bis ( N 4 -methylthiosemicarbazone) ( 64 Cu-ATSM) is a potential theranostic agent targeting the over-reduced state under hypoxia within tumors. Recent clinical Cu-ATSM positron emission tomography studies have revealed a correlation between uptake and poor prognosis; however, the reason is unclear. Here, using a human colon carcinoma HT-29 model, we demonstrated that the intratumoral 64 Cu-ATSM high-uptake regions exhibited malignant characteristics, such as upregulated DNA repair and elevated %CD133 + cancer stem-like cells. Based on this evidence, we developed a strategy to enhance the efficacy of 64 Cu-ATSM internal radiotherapy (IRT) by inhibiting DNA repair with a nucleic acid (NA) antimetabolite. The results of the analyses showed upregulation of pathways related to DNA repair along with NA incorporation (bromodeoxyuridine uptake) and elevation of %CD133 + cells in 64 Cu-ATSM high-uptake regions. In an in vivo 64 Cu-ATSM treatment study, co-administration of an NA antimetabolite and 64 Cu-ATSM synergistically inhibited tumor growth, with little toxicity, and effectively reduced %CD133 + cells. 64 Cu-ATSM therapy targeted malignant tumor regions with activated DNA repair and high concentrations of CD133 + cells in the HT-29 model. NA antimetabolite co-administration can be an effective approach to enhance the therapeutic effect of 64 Cu-ATSM IRT.